Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/vop.12633
|View full text |Cite
|
Sign up to set email alerts
|

Spectral domain optical coherence tomography evaluation of the feline optic nerve and peripapillary retina

Abstract: Objective To describe and to establish normative data for the feline optic nerve and peripapillary retina using SD‐OCT (Spectralis® HRA+OCT2). Methods Slit‐lamp biomicroscopy and rebound tonometry were performed in seven male‐intact (0.65 ± 0.02 years;4.34 ± 0.33 kg) and seven female‐spayed (0.74 ± 0.03 years; 3.13 ± 0.28 kg) cats. All eyes were pharmacologically dilated with 1% tropicamide prior to indirect ophthalmoscopy examination. Animals were then placed under general anesthesia. Optic nerve and peripapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
(85 reference statements)
1
6
0
Order By: Relevance
“…Diffusion weighted imaging provides an alternative approach to early evaluation of glaucoma, a group of diseases characterized by the loss of RGCs and their axons. The technique we describe does overcome a major limitation associated with OCT, which is increasingly reported in the veterinary literature for assessment of the retina and ONH 46‐63 . Canine glaucoma is commonly associated with corneal opacities and drug‐induced miosis which both preclude reliable OCT assessment, but do not affect measurements of the white matter tracts using DTI.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion weighted imaging provides an alternative approach to early evaluation of glaucoma, a group of diseases characterized by the loss of RGCs and their axons. The technique we describe does overcome a major limitation associated with OCT, which is increasingly reported in the veterinary literature for assessment of the retina and ONH 46‐63 . Canine glaucoma is commonly associated with corneal opacities and drug‐induced miosis which both preclude reliable OCT assessment, but do not affect measurements of the white matter tracts using DTI.…”
Section: Discussionmentioning
confidence: 99%
“…De Ramus et al 30 presented a uniform standard for murine OCT layer nomenclature, in which they identified the choroid as an intensely hyperreflective band directly external to the RPE/BM. Detailed images of outer retinal layer anatomy visible on canine 1,10,17,21,31–34 and feline 16,35 SD‐OCT scans have been published. Unfortunately, a consensus nomenclature of the outer retinal bands distinguishable on SD‐OCT scans, similar to that in humans 29 and mice, 30 has not been established in other species.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that spectral domain OCT (SD-OCT) is a reliable method to evaluate different retinal layers and optic nerve morphology in colobomas in dogs, 15 in healthy or glaucomatous cats. [16][17][18] Recently, it has been published that outer retinal band and choriocapillaris can be identified in healthy dogs and cats, 19 and different vascular layers of the retina and choroid are nicely evaluated by OCT-A in cats. 20 The present report describes the clinical case of bilateral corneal dermoids associated with bilateral choroidoscleral colobomas in a cat, its SD-OCT fundus evaluation, the surgical outcome and the follow-up of lesions up to 18 months.…”
Section: Introductionmentioning
confidence: 99%